Review of Philip Rupprecht. 2001. Britten’s Musical Language. Cambridge: Cambridge University Press - Whitesell, Lloyd (Current Musicology, 2002)
In this wonderful book Philip Rupprecht develops a new, unified theoretical approach to Britten’s dramatic vocal music. To that end, he assembles a chronological series of close readings of major works, some extremely well-known (Peter Grimes, Billy Budd, The Turn of the Screw, War Requiem), others less familiar (Curlew River, Death in Venice). His approach draws on speech-act theory, as expounded by J. L. Austin (1975) and John Searle (1969) , conceiving linguistic utterance as a performative act. This conceptual basis resituates traditional concerns of text-setting, tonal structure, and leitmotivic development by promoting the dramatic context as the central topic of analysis. The focus shifts from details of objective structural integrity to rhetorical effects. Music, words, and gesture are treated not as separable symbolic media but as elements of a composite interactional discourse with “social and institutional force” (3). Broadly speaking then, the book aims toward a renewed evaluation of Britten’s stature as a dramatic composer while arguing persuasively for the value of linguistic and literary theories in music scholarship.